Central Asian Sources and Central Asian Research Selected Proceedings from the International Symposium "Central Asian Sources and Central Asian Research", October 23rd-26th, 2014 at Göttingen State and University Library - Reckel, Johannes (Universitätsverlag Göttingen, 2016)
In October 2014 about thirty scholars from Asia and Europe came together for a conference to discuss different kinds of sources for the research on Central Asia. From museum collections and ancient manuscripts to modern newspapers and pulp fiction and the wind horses flying against the blue sky of Mongolia there was a wide range of topics. Modern data processing and data management and the problems of handling five different languages and scripts for a dictionary project were leading us into the modern digital age. The dominating theme of the whole conference was the importance of collections of source material found in libraries and archives, their preservation and expansion for future generations of scholars. Some of the finest presentations were selected for this volume and are now published for a wider audience.